Pengabdian Kepada Masyarakat Melalui Penyuluhan Hukum “Kesadaran Hukum dalam Melakukan Mediasi Sengketa Lahan di Desa Tanjung Limau” - Fahrul Rozy; Ni Kadek Dwita Suardianti; Mai Lidya; Siti Faricha Andi Adkha; Ziana Walidah; Zulham Puluadji; Abdul Muhazir; Desi Wilda Rizki Amelia; Rizqi Ramadhan Pohan (Jurnal Pengabdian Masyarakat Waradin, 2024)
Community service through the Real Work Lecture (KKN) program is one way for students to contribute to overcoming various problems faced by society. One of the problems encountered in Tanjung Limau Village is land disputes. Land disputes are a problem that often occurs in various regions, especially in developing countries like Indonesia. This conflict can arise due to unclear ownership status, overlapping claims, or government policies that do not support the community. This research aims to determine the process of resolving land disputes in Tanjung Limau Village through mediation. Tanjung Limau Village, located in Muara Badak District, Kutai Kertanegara Regency, East Kalimantan Province, faces complex land disputes. Many residents do not have legal proof of land ownership, such as a Certificate of Ownership (SHM) or Statement of Physical Land Control (SPPFBT). This triggers endless disputes in society. This research uses research methods with a sociological juridical approach. Data was collected through observations and interviews with village officials, RT heads, and residents of Tanjung Limau Village. The data was then processed using qualitative descriptive methods. The research results show that many land disputes in Tanjung Limau Village are resolved through mediation. Mediation was chosen because it was considered more effective and efficient than litigation. Legal education with the theme "Legal Awareness in Mediating Land Disputes" was held to increase public understanding of the importance of mediation in accordance with legal procedures. This research found that the option of resolving land disputes through mediation has advantages because it can lead the parties to the realization of a permanent and sustainable peace agreement. Mediation is also an important step to be taken by parties involved in court proceedings, so that it can reduce the burden of cases in court and strengthen the function of court institutions in resolving disputes.